Eco Kids, Ano 3, Número 1, Agosto de 2016, Encruzilhada/BA - (:unkn) unknown (Ministério Público do Estado da Bahia, 2016)
No abstract.
Keywords: Fauna; Flora; Nascente - Rios; Meio Ambiente; Caatinga; Educação ambiental; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO